Synthesis and Characterisation of Co(II), Ni(lI) and Cu(II) Complexes of Some 6-Aryl-5-bexene-2,4-diones. - PAUL, MATHEW; KRISHNANKUTTY, K. (Asian Journal of Chemistry, 2010)
A series of 6-aryl-5-hexene-2,4-diones and their Co(II), Ni(lI) and Cu(ll) complexes of ML2 stoichiometry have been synthesized and characterised. The elecronic, ir, 1H NMR, mass spectral and thennogravimetric data are discussed.